1996
DOI: 10.1111/j.1439-0507.1996.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological investigations in vaginal mycoses*

Abstract: In 42 women with chronically recurrent and 20 women with acute Candida albicans vulvovaginitis, as well as 14 women with Candida glabrata vaginitis, the following investigations were carried out: determination of protein content and secretory immunoglobulin A (sIgA) in the cervicovaginal secretion by a self-modified ELISA technique; determination of immunocells and cellbound IgA in the cervicovaginal secretion by immunofluorescence and nephelometric analysis of IgA in the serum. The results were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(1 reference statement)
0
9
0
2
Order By: Relevance
“…Anti-Candida IgG and IgA have been identified in the sera and cervicovaginal secretions of women with and without RVVC (30,67,166,170). While serum anti-Candida IgA and IgG levels appear to be similar in women regardless of a history of RVVC, some studies have shown higher levels of vaginal anti-Candida IgA and IgG in women with RVVC than in those without RVVC (67), whereas others have not found such differences (30,91,170). Thus, a potential role of local Abs in RVVC is dismissed by most authors.…”
Section: Humoral Immune Responses To Vvcmentioning
confidence: 99%
“…Anti-Candida IgG and IgA have been identified in the sera and cervicovaginal secretions of women with and without RVVC (30,67,166,170). While serum anti-Candida IgA and IgG levels appear to be similar in women regardless of a history of RVVC, some studies have shown higher levels of vaginal anti-Candida IgA and IgG in women with RVVC than in those without RVVC (67), whereas others have not found such differences (30,91,170). Thus, a potential role of local Abs in RVVC is dismissed by most authors.…”
Section: Humoral Immune Responses To Vvcmentioning
confidence: 99%
“…Another approach that has been tried is the development of antibodies to limit the effect of the Thelper (TH)-2 response and increase the TH-1 response, which is beneficial to the course of the disease [108,109] . Vaccination with different substances to increase IL-12 as well as exogenous application of IL-12 have been tried to increase the TH-1 response and hence improve the course of RVC in mice, with various levels of success [110] .…”
Section: Hormones and Contraceptionmentioning
confidence: 99%
“…Differentiation between C. albicans serotypes is based on the presence of ␤-1,2-oligomannosides in serotype A mannan. Serotyping methods have been used for epidemiological studies for a long time and have revealed differences in the geographic distributions of different strains (5) and their abilities to infect immunocompetent or immunocompromised patients (6,11,27). However, immunochemical studies have shown that serotype A strains do not express antigen 6 when they are grown at a low pH or a high temperature.…”
mentioning
confidence: 99%